A multi-criteria decision-making approach for wheelchair selection using intuitionistic fuzzy TOPSIS - Dhala, Prasant Ranjan; Choudhury, Bibhuti Bhusan; Pamucar, Dragan; Simic, Vladimir; Sahoo, Sushil Kumar (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: Selecting an appropriate wheelchair is vital for ensuring mobility, comfort, and independence for individuals with disabilities. The primary objective is to assist in identifying the optimal wheelchair by considering a range of user-centric criteria and mitigating decision-making ambiguities.Methods: The proposed framework leverages intuitionistic fuzzy sets to account for the hesitancy and imprecision often present in decision-making. Criteria weights and alternative evaluations were determined with expert input. Sensitivity analysis was conducted to ensure the robustness and reliability of the ranking process. A case study was performed to validate the effectiveness of the methodology and to illustrate its practical application.Results: The study demonstrated that AI-powered wheelchairs (APWs) outperformed other wheelchair options based on the selected criteria and sub-criteria.Conclusion: The findings highlight the utility of the Intuitionistic Fuzzy TOPSIS approach in facilitating well-informed wheelchair selection decisions. This method benefits end users, caregivers, and medical professionals by addressing the complexities of subjective and uncertain decision-making, ultimately leading to more inclusive and reliable outcomes. The framework proves to be an effective tool for improving the decision-making process in wheelchair selection.
Keywords: Wheelchair Selection; Intuitionistic Fuzzy; Triangular Fuzzy; TOPSIS; Sensitivity Analysis